Consumerism in world history - Stearns, Peter N., author. Link
1 online resource
Keywords: "The third edition of Consumerism in World History explores the nature of consumerism and its evolution, with particular emphasis on the modern "consumer revolution" and its global scope. The book deals with crucial interpretive issues, such as whether consumerism is a natural human expression or involves other causes, the relationship between consumer apparatus (such as shops and advertising) and human needs, and the interplay between Western and other regional forms of consumerism. It covers major historical moments and changes, including the consumer revolution in Western society beginning in the 17th century and regional cultural patterns from the 19th century onward. This is a substantially revised edition, with updated suggested readings, rewritten sections on premodern consumerism in agricultural societies and globalization and consumerism, and expanded coverage of major regions like India and Latin America. This volume is essential reading for all students of world history and will be of great value to those in business history and environmental history"--